Optimalisasi Peran Kader Melalui Pengenalan E-Kriting dan Pembuatan Madu Soya Bean Dalam Upaya Skrining dan Pencegahan Stunting - Yuniza, Yuniza; Sukron, Sukron; Fadillah, Arif; Putri, Rosmitha Aizah (Journal of Community Development, 2025)
Dusun VI Sungai Pinang, Banyuasin Regency, South Sumatra, there is a PKK mothers' association that is part of the Health care mothers. PKK mothers do not yet understand stunting prevention. The stunting data collection process is still done manually by recording in notebooks and sometimes the notes used are lost. Ekriting (electronic stunting screening) and soya bean honey are solutions in preventing stunting. Ekriting is a media that can be used by PKK mothers to screen toddler growth and development (TB and BB). Preventing stunting is important by providing nutrition for 1000 days of life and providing proper nutrition to pregnant women. One of the nutrients that can be easily obtained is honey and soybeans. The sampling method uses total sampling, meaning taking all PKK mothers who are part of the Health care mothers. The results of this Community Service activity are that most cadres (80%) know about stunting prevention with adequate nutrition and cadres know about stunting screening using the application. The assessment uses a questionnaire found in the stunting prevention application. Conclusion There is an Increase in the Role of Cadres Through the Introduction of E-Kriting and Making Soya Bean Honey in Stunting Screening and Prevention Efforts.